The mitral valve prolapse frequency in healthy females with generalized joint hypermobility: A case-control study - Hande Özdemir; Filiz Tuna; Meryem Aktoz; Nurettin Taştekin; Derya Demirbağ Kabayel (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to investigate the frequency of mitral valve prolapse between healthy females with generalized joint hypermobility and healthy controls. Patients and methods: This observational, cross-sectional, controlled study included female individuals with generalized joint hypermobility (n=39, mean age: 20.5±1.1 years; range, 19 to 23 years) and healthy controls (n=42, mean age: 20.6±1.2 years; range, 18 to 23 years) between July 2017 and November 2017. The generalized joint hypermobility consisted of women with a Beighton score of ≥4, while the control group consisted of women with a Beighton score of ≤3. Echocardiography was performed to all participants. Mitral valve prolapse was defined as having single or bileaflet prolapse of at least 2 mm beyond the long-axis annular plane with or without mitral leaflet thickening. Results: No significant difference was found in the age, height, body weight, and body mass index between the groups (p>0.05). The median Beighton score was 5 in the generalized joint hypermobility group and 2 in the control group. No mitral valve prolapse was detected in those with generalized joint hypermobility, while non-classical mitral valve prolapse was observed in one participant in the control group, indicating no statistically significant difference between the two groups (p>0.05). Conclusion: Our study results suggest that the frequency of mitral valve prolapse is comparable between the women with generalized joint hypermobility and healthy controls. Based on these results, routine assessment of mitral valve prolapse is not recommended in this population.